(PENSION RETIREMENT IN ISLAMIC JURISPRUDENCE AND THAILAND LABOUR LAW) - Abdulsoma, Thoarlim; Ahmad Farid, Ibrahim (2018)
A pension retirement is a type of insurance and termination indemnity if the specified conditions are met. The worker is entitled to the sum of the money, or to the dependents, that the pension is a sum of money due to the employee or employee after the termination of employment or when he reaches a certain age or because of his retirement from work, and pension also guaranteed until the death of the person, and under the Thailand Labor Law on pensions and retirement they did not address for civil institutions or companies because workers or employees in enterprises or companies did not have a pension and retirement scheme.The methodology used by the researcher in the preparation of this research is under two methodology: first the Inductive Method, under this method the researcher tried to deduce first the texts of the Holy Quran, then the Prophetic Sunnah (Hadith), and then the sources of other Islamic legislation that related to the subject, and the second method is the Descriptive Analytical Approach. The researcher in this study analyzed the views of the scholars on the subject. All statements and evidence are stated along with indications of the evidence of relation and mental evidence that we need, and the most important findings of the study is to say that the jurists have entered the pension after the completion of his service, we find that the law has a defect and lack of reality on this matter, and the end of service reward in Islamic jurisprudence, we find that the worker is entitled to reward end of his service if the conditions are met, and the remuneration from either the State or the company or factories paid at the end of the work, and the end of service and the beneficial in the Thailand Labor Law has addressed under Article (118) and it depends on the workers according to the length and time of work if they are working for the long term they will receive the end of service reward at a large amount. May Allah Bless our Prophet Muhammad SAW and his all families and companions. Praise be to Allah, Lord of the Worlds